2014
DOI: 10.3174/ajnr.a4011
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic Xanthoastrocytoma of Childhood: MR Imaging and Diffusion MR Imaging Features

Abstract: BACKGROUND AND PURPOSE: Pleomorphic xanthoastrocytomas are rare astrocytic neoplasms of childhood and young adulthood. The purpose of this retrospective review was to evaluate MR imaging features of pediatric pleomorphic xanthoastrocytomas with an emphasis on diffusion MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 16 publications
1
20
0
2
Order By: Relevance
“…Hemorrhage in PXAs has been described as an uncommon finding, but it was present in 18% of tumors in our series. And a study of PXAs in childhood also reported 33% of the patients had hemorrhage 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemorrhage in PXAs has been described as an uncommon finding, but it was present in 18% of tumors in our series. And a study of PXAs in childhood also reported 33% of the patients had hemorrhage 4 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 21% of PXA cases in children and adolescents had anaplastic features or malignant transformation at initial presentation 6 . A study dedicated solely to pediatric PXAs found that 27% of cases had anaplastic features 4 . This entity has now been acknowledged and included in the 2016 update of the WHO Classification of Tumors of the CNS as Grade III anaplastic PXA 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The histopathologic characteristics of our patient cohort are summarized in Table 1 Given the rarity of aPXA tumors, reports in the literature are scarce and many are limited in design to small case reports. 10,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] As a result, current understanding of aPXA tumors is incomplete. In one of the larger case series published on aPXA (33 patients), a multivariate analysis by Ida and colleagues demonstrated that OS was significantly lower in the aPXA cohort when compared to PXA.…”
Section: Histopathologymentioning
confidence: 99%
“…Lezyonun solid bileşeni, gri cevhere kıyasla, T1A serilerde izo-hipointens, T2A serilerde izo-hafif hiperintens olarak izlenir. Lezyon çevresinde minimal veya belirgin derecede ödem izlenebilir [19]. Hemoraji tipik olmamakla birlikte, görülebilir.…”
Section: Pleomorfik Ksantoastrositomunclassified